Sistem Pendukung Keputusan Dalam Pemilihan Santri Teladan Menerapkan Metode ELECTRE - Gusnia Ariyanti Lestari (Journal of Information System Research (JOSH), 2021)
Islamic boarding schools are Islamic educational institutions. The Islamic boarding school education system is one where students will be selected and entitled to be model students and given awards every year. The educational strategy adopted so far is general in nature, providing standard or average treatment to all students, so they do not pay attention to the differences between students in their skills, interests and talents. With this kind of strategy, excellence will emerge randomly and is highly dependent on students' motivation to learn. Exemplary students must meet several criteria, namely memorization of the book, discipline, morals, and achievement. Therefore, it needs to be developed to the superior that is owned by each student so that it can be converted into a superior achievement in order to motivate students to continue to excel, AL-HUSNA Islamic boarding school conducts activities to develop the potential of students through the selection of exemplary students. A decision support system (SPK) to facilitate the selection of exemplary students and utilize Eliminition and Choice Translation Reality (ELECTRE) as a method of decision. The ELECTRE (Eliminition and Choice Translation Reality) method can be used in assessing and ranking based on strengths and weaknesses through pairwise comparisons on the same criteria